Predictors of adverse outcome in patients with arrhythmogenic right ventricular dysplasia/cardiomyopathy: long term experience of a tertiary care centre. Issue 9 (15th August 2005) - Lemola, K; Brunckhorst, C; Helfenstein, U; Oechslin, E; Jenni, R; Duru, F
Abstract : Objective: To investigate the predictors for adverse clinical outcome in patients with arrhythmogenic right ventricular dysplasia/cardiomyopathy (ARVD/C) during long term follow up. Methods: 61 patients with ARVD/C were studied to assess the impact of family history, clinical findings, surface ECG parameters, echocardiographic findings, and electrophysiological findings on clinical outcome. The prevalence of these risk factors were compared in two patient groups: group A (patients with adverse clinical outcome: sudden cardiac death, death from heart failure, or heart transplant) and group B (survivors excluding patients who received a heart transplant). Results: Mean age at first diagnosis was 44 (14) years. The mean follow up duration was 55 (47) months. Ten patients (16%) died during follow up. The cause of death of eight of these patients was probably arrhythmic. Two patients died of advanced heart failure. Five patients underwent heart transplantation because of terminal heart failure. Risk factors significantly associated with adverse outcome were history of congestive heart failure (p < 0.001), the presence of left ventricular involvement on echocardiography (p < 0.001), left atrial dilatation (p < 0.05), prolonged PR duration (p < 0.01), prolonged QRS in V1 (p < 0.05), and bundle branch block (p < 0.05). In multivariate analysis, history of congestive heart failure and presence of left ventricular involvement were identified as independent risk predictors for an adverse outcome. Conclusions: Congestive heart failure and left ventricular involvement are independently associated with adverse outcome in patients with ARVD/C during long term follow up.